Pengaruh Intensitas Belajar Dan Lingkungan Sekolah Terhadap Hasil Belajar Peserta Didik Pada Materi Sholat Fardhu - Novita Diana Sari; Sukma Eka Wijaya; Tamama Hafizah; Rani Selviani; Guntur Gunawan; Muhammad Istan; Paidi Gusmuliana (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This study discussed whether there was an influence of study intensity and school environment on student learning outcomes in the subject of Fardhu Prayer at SMP Negeri 05 Lebong. The purpose of this study was to determine how study intensity and the environment influenced student outcomes in the Fardhu Prayer material. The sampling technique used was a questionnaire with the researchers' source being seventh grade students, and observations were also utilized. The analytical tools used included SPSS with Descriptive Analysis, Inferential Analysis, T-test, and F-test as the analysis methods, along with the Pearson product-moment correlation technique. This research shows that study intensity, school environment, and learning outcomes reveal significant findings that indicate a strong and positive influence of several factors on student learning outcomes in the subject of Fardhu Prayer. Through the t-test, it is found that both study intensity and the school environment individually have a significant impact, with a t-value of 3.225 each, far exceeding the t-table value of 1.664 and a p-value of 0.002. Furthermore, the F-test, which combines both variables, shows an F-value of 7.242, exceeding the F-table value of 3.12 and a very low p-value (0.001), indicating an effective synergy between the two factors in enhancing material understanding. These results affirm the importance of intensifying efforts to maintain a conducive learning environment and encouraging students to increase their study intensity to achieve optimal learning outcomes.